Integrated genome analysis of uterine leiomyosarcoma to identify novel driver genes and targetable pathways. Issue 6 (7th November 2017) - Cuppens, Tine; Moisse, Matthieu; Depreeuw, Jeroen; Annibali, Daniela; Colas, Eva; Gil‐Moreno, Antonio; Huvila, Jutta; Carpén, Olli; Zikán, Michal; Matias‐Guiu, Xavier; Moerman, Philippe; Croce, Sabrina; et al.
Abstract : Uterine leiomyosarcomas (uLMS) are rare, aggressive malignancies for which limited treatment options are available. To gain novel molecular insights into uLMS and identify potential novel therapeutic targets, we characterized 84 uLMS samples for genome‐wide somatic copy number alterations, mutations, gene fusions and gene expression and performed a data integration analysis. We found that alterations affecting TP53, RB1, PTEN, MED12, YWHAE and VIPR2 were present in the majority of uLMS. Pathway analyses additionally revealed that the PI3K/AKT/mTOR, estrogen‐mediated S‐phase entry and DNA damage response signaling pathways, for which inhibitors have already been developed and approved, frequently harbored genetic changes. Furthermore, a significant proportion of uLMS was characterized by amplifications and overexpression of known oncogenes ( CCNE1, TDO2 ), as well as deletions and reduced expression of tumor suppressor genes ( PTEN, PRDM16 ). Overall, it emerged that the most frequently affected gene in our uLMS samples was VIPR2 (96%). Interestingly, VIPR2 deletion also correlated with unfavorable survival in uLMS patients (multivariate analysis; HR = 4.5, CI = 1.4–14.3, p  = 1.2E‐02), while VIPR2 protein expression was reduced in uLMS vs . normal myometrium. Moreover, stimulation of VIPR2 with its natural agonist VIP decreased SK‐UT‐1 uLMS cell proliferation in a dose‐dependent manner. These data suggest that VIPR2, which is a negative regulator of smooth muscle cell proliferation, might be a novel tumor suppressor gene in uLMS. Our work further highlights the importance of integrative molecular analyses, through which we were able to uncover the genes and pathways most frequently affected by somatic alterations in uLMS. Abstract : What's new? The molecular genetic basis of uterine leiomyosarcoma (uLMS), a rare but extremely lethal cancer type, remains poorly characterized. Through an integrated analysis of genomic and transcriptomic data generated in a large cohort of 84 uLMS patients, here the authors identified several cancer driver genes contributing to uLMS. Most of these genes are known cancer drivers ( TP53, RB1, etc.), whereas several others ( CCNE1, FGFR, etc.) represent potential therapeutic targets for which drugs are already available or being developed. The data also identified VIPR2, a negative regulator of smooth muscle cell proliferation, as a potential novel tumor suppressor gene in uLMS.